Color image encryption method based on four-dimensional multi-scroll multi-wing hyperchaotic system and DNA mutation mechanism - Qi Peng; Kun Zhang; Bing Zheng; Hao Ning; Yu Zhou; Xin Xie (Journal of King Saud University: Computer and Information Sciences)
Abstract With the increasing demand for secure multimedia data transmission, chaotic systems have attracted widespread attention due to their sensitivity to initial conditions and pseudo-randomness. However, traditional low-dimensional chaotic systems often suffer from limited complexity and predictability, making them insufficient for high-security image encryption applications. To enhance the practicality and security of chaotic systems in the field of image encryption, this paper proposes a novel four-dimensional multi-scroll multi-wing hyperchaotic system and a corresponding color image encryption algorithm incorporating a DNA mutation mechanism. First, A nonlinear coupling term and an external periodic modulation factor are introduced into the Lorenz system to construct a four-dimensional multi-scroll multi-wing hyperchaotic system. This system features 16-wing symmetric attractors, time-varying equilibrium points, and complex dynamical behavior. Its hyperchaotic properties and nonlinear evolution characteristics are validated using Lyapunov exponent spectra, bifurcation diagrams, phase portraits, and Poincaré sections. Subsequently, based on this system, a DNA-based image encryption framework is proposed by combining DNA computing with gene mutation mechanisms. The encryption scheme includes two-level scrambling, self-feedback, inter-channel cross diffusion, and a key-controlled DNA mutation module. Experimental results show that the algorithm achieves excellent performance in information entropy, NPCR/UACI, and key sensitivity, demonstrating its effectiveness and robustness for image information protection.